Adrenal Scintigraphy in Primary Aldosteronism - Hoefnagels, W. H.; Claessens, R.A.; Corstens, F.H.; Drayer, J.I.; Kazem, I.; Kloppenborg, P.W. (Nuklearmedizin - NuclearMedicine, 1981)
Dexamethasone-modified adrenal scintigrams were performed on 13 patients with an aldosterone-producing adenoma and on one patient with an aldosterone-producing carcinoma. Adrenal scintigrams using 131I-19-Iodocholesterol were obtained after short pre-treatment with dexamethasone, while 131I-6ß-Iodomethyl-19-Nor-Cholesterol scintigrams were performed after long-term pre-treatment with dexamethasone during 9–21 days. Using the former procedure the adrenal scintigrams correctly identified the adenoma in 3 of 8 patients, while with the latter procedure the adrenal scintigrams localized the adenomas in 8 out of 9 patients, including 3 patients in whom the former procedure had failed. The adrenal carcinoma was not visualized with 131I-6ß-Iodomethyl-19-Nor-Cholesterol. Thus, the sensitivity of 131I-19-Iodocholesterol scintigrams to detect aldosterone-producing adenomas was only 37.5%. Uptake of radioactivitiy in the normal contralateral adrenal gland accounted for the low detection rate. On the other hand, the 131I-6ß-Iodomethyl-19-Nor-Cholesterokl scintigrams, performed after long-term pre-treatment with dexamethasone, had a sensitivity of 89%. It is suggested that long-term pre-treatment with dexamethasone contributed to the improved sensitivity by a more effective suppression of radioactivity uptake in the normal adrenal gland.